2021
DOI: 10.1016/j.gore.2021.100868
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on the impact of long-distance travel for gynecologic cancer care

Abstract: Highlights Barriers to travel included time, cost, companionship, navigation, and physical discomfort. Social support was an important facilitator of travel for care. A significant minority of patients preferred in-person visits to telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Qualitative studies examining the role of travel burden and access to care in surgical decision making may help contextualize our understanding of these factors as decision-making factors among rural women electing CPM. Among rural women with gynecologic cancers, for example, one qualitative study found that recommendations from physicians and others were the primary drivers of travel, despite the associated burdens [39]. Studies like this among rural women electing CPM may help identify intervention strategies to reduce guideline non-concordant CPM among this population.…”
Section: Discussionmentioning
confidence: 97%
“…Qualitative studies examining the role of travel burden and access to care in surgical decision making may help contextualize our understanding of these factors as decision-making factors among rural women electing CPM. Among rural women with gynecologic cancers, for example, one qualitative study found that recommendations from physicians and others were the primary drivers of travel, despite the associated burdens [39]. Studies like this among rural women electing CPM may help identify intervention strategies to reduce guideline non-concordant CPM among this population.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, we can assume that patients for whom distance was a problem preferred a closer hospital. In a recent qualitative study, Mujumdar et al 28 highlighted that some women with gynaecological malignancies might prefer to be cared at a referral centre despite a longer travel time.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative interview study recruited 19 women that traveled an average of 87 miles to receive gynecologic oncology care. The study revealed themes of timing and the need to coordinate a companion as barriers to receiving care and reported that most patients had to utilize personal resources or utilize community programs (similar to Family House at UPMC) in order to participate in non-surgical care away from home [ 32 ]. This study corroborated the perspective of interviewed physicians that social support was essential for patients that had to travel for oncologic care.…”
Section: Discussionmentioning
confidence: 99%